2002
DOI: 10.1074/jbc.m207160200
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin Expression Is Regulated by Transcriptional Cooperation between the Hypoxia and Transforming Growth Factor-β Pathways

Abstract: Endoglin is a transforming growth factor-␤ (TGF-␤) co-receptor expressed mainly on endothelial cells and involved in cardiovascular development, angiogenesis, and vascular remodeling. This is illustrated by the fact that mutations in the endoglin gene give rise to hereditary hemorrhagic telangiectasia type 1, a dominant vascular disease with clinical manifestations that originate by a mechanism of haploinsufficiency. Thus, studies on the regulated expression of endoglin are crucial to devising therapeutic stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
214
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(224 citation statements)
references
References 75 publications
7
214
0
1
Order By: Relevance
“…ALK5 (TGFBR1) is expressed in myeloma cells and is capable of being activated in response to TGF-β. [39] Both myeloma cell lines and primary cells were shown to express TGF-β mRNA and active protein, [40,41] however it was also reported that myeloma cells do not produce active TGF- Expression of the other type 3 receptor, endoglin, is induced by TGF-β and hypoxia, [44,45] and increased levels of soluble endoglin in myeloma patients were associated with advanced disease and tumor growth. [46,47] Membrane-bound endoglin is found on some myeloma cell lines, but lack on others.…”
Section: Expression Of Related Receptors and Ligandsmentioning
confidence: 99%
“…ALK5 (TGFBR1) is expressed in myeloma cells and is capable of being activated in response to TGF-β. [39] Both myeloma cell lines and primary cells were shown to express TGF-β mRNA and active protein, [40,41] however it was also reported that myeloma cells do not produce active TGF- Expression of the other type 3 receptor, endoglin, is induced by TGF-β and hypoxia, [44,45] and increased levels of soluble endoglin in myeloma patients were associated with advanced disease and tumor growth. [46,47] Membrane-bound endoglin is found on some myeloma cell lines, but lack on others.…”
Section: Expression Of Related Receptors and Ligandsmentioning
confidence: 99%
“…One potential factor that is able to increase the expression of endoglin is the receptor ligand TGF-␤ itself. In endothelial cells, monocytic cells, human mesangial cells, and cultured cell lines, TGF-␤ is able to upregulate promoter activity and endoglin expression (75)(76)(77)(78)(79). Because it is well documented that activated HSC and MFB produce large amounts of TGF-␤ (52, 80), endoglin expression could be maintained during transdifferentiation by persistent autocrine stimulation by TGF-␤.…”
Section: Fig 9 Surface Exposition Of Endoglin In Hsc/mfbmentioning
confidence: 99%
“…17 These angiogenesis inhibitors are released under inflammatory state. 18,19 These circulating proteins have been shown to have pathogenetic roles in hypertension in preeclampsia, 20 in human chronic kidney disease, 21 coronary artery disease 22 and in animal models of hypertension. 23,24 However, none of the studies have examined the relationship between endothelial dysfunction and hypertension in relationship to hypoxia exposure in OSA patients.…”
Section: Introductionmentioning
confidence: 99%